Comparative transcriptome analysis reveals key candidate genes mediating ovarian development in Spodoptera frugiperda fed on two host plants - Zheng, Renwen; Yao, Ling; Peng, Jun; Chen, Zihan; Yang, Fan; Chen, Shuxian; Tang, Qingfeng (Frontiers in Physiology, 2022)
Fall armyworm (FAW) (Spodoptera frugiperda) is a highly polyphagous lepidopteran pest, with its growth and adaptation affected by different hostplants. However, little is known about the effects of host plants on ovarian developmentin this species. Thus, we evaluated the effects of feeding on corn (Zea mays L.) and goosegrass (Eleusin indica), on the ovarian development of S. frugiperda. Using various stages of S. frugiperda, we also evaluated the larval and pupa weight, number of eggs, and differentiation of ovarioles over time. Results showed that females fed on goosegrass had shorter ovarioles and laid less eggs compared to those fed on corn. Transcriptome analysis identified 3213 genes involved in ovarian development in the fall armyworm. Of these, 881 genes were differentially expressed when feeding on corn and goosegrass. The analysis also indicated that the hormone biosynthetic pathways may be involved in reproductive system. In relation to reproductive function, 9 juvenile hormone (JH) biosynthetic genes, 4 20-hydroxyecdysone (20E) biosynthetic genes, and 4 ovary relevant functional genes were identified. The time course of the expression profiles of these hormone and ovary-development related genes were measured by quantitative real-time PCR (qRT-PCR). Six of them showed a decreasing trend in the ovary of FAW fed on goosegrass, while 2 genes showed an increasing trend. Our results showed that significant changes in the reproductive activity/ovary development in the FAW occurred, in response to different diets. These results serve as bases for evaluating how optimal host plants and feeding preference affect ovarian development in the FAW.